Intonation contours and stress group patterns in declarative sentences of varying length in ASC Danish - Thorsen, Nina (Annual Report of the Institute of Phonetics University of Copenhagen, 1980)
Four subjects recorded eight non-compound declarative sentences, containing from one to eight stress groups. Acoustic analysis reveals a tendency for fundamental frequency range to increase with increased utterance length, but in a non-linear and seemingly random fashion. The increase is brought about by higher starting points as well as lower ending points in the longer utterances. Concomitant with the range increase we find a decrease in overall downdrift in the longer utterances, but degree of downdrift is not simply inversely related to utterance length. With four and more stress groups the intonation contour is decomposed into prosodic phrase groups, i.e. the contour contains discontinuities in the shape of partial resettings. The prosodic phrase group boundaries are determined by but do not exactly coincide with major syntactic boundaries, and the data present an argument in favour of a hypothesis of prosodic categories as distinct entities with a non-isomorphous relation to syntactic structure.